Knowledge, power and powerful knowledge re-visited. Issue 2 (3rd April 2019) - Muller, Johan; Young, Michael
Abstract: This article extends the authors' earlier work (Young & Muller 2013) exploring the concept of 'powerful knowledge'. It first examines some of the origins of the concept and goes on to a brief consideration of how sociology, political theory and economics have traditionally represented 'power' and 'knowledge'. Two key senses of power are identified and two difficulties are next identified: how to retain both senses of power in a satisfactory account of 'powerful knowledge; and how to provide a satisfactory account of the 'power' of knowledge in the humanities. By identifying three meanings of 'powerful knowledge', and making an argument for their interrelationship, the article aims to put the concept on a firmer footing and point to its potential implications for curriculum theory.